Urinary polycyclic aromatic hydrocarbon metabolites are positively related to serum testosterone levels of males and serum estradiol levels of females among U.S. adults - Yuan, Qiming; Jin, Kun; Zhou, Xianghong; Qiu, Zhimei; Li, Jiakun; Jin, Di; Zhang, Zilong; Zhang, Chichen; Yang, Lu; Zhan, Yu; Qiu, Shi; Wei, Qiang (Frontiers in Endocrinology, 2022)
Background: It has been reported for several years that polycyclic aromatic hydrocarbons (PAHs) could disturb human endocrine function. However, there is still a short of consistent conclusion about the relationship between PAH exposure and levels of sexual hormones. The aim of our study is to explore whether exposure to PAHs and how PAHs affect the levels of serum testosterone (T) and estradiol (E2) in adults, hoping to fulfill the knowledge gap. Materials and methods: This study included adults aged 20 and above who participated in the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2016. We included 10 PAH metabolites in this study. The levels of urinary PAH metabolites were log-transformed and divided into quartiles. The associations between PAH metabolites and both serum T levels of males and E2 levels of females were investigated using multivariate regression models. We furtherly calculated PAHs scores by sum of ranks across 10 PAHs metabolites, which represented the exposure levels of PAHs mixtures, and the association between PAHs scores and serum T and E2 levels were analyzed. Results: A total of 4,654 subjects were included in this study, including 2,460 males and 2,194 females. After adjusting for confounders, 2-hydroxynapthalene and 3-hydroxyfluorene were positively associated with serum T levels of males (p-value for trend=0.047, and p-value for trend=0.006, respectively), while 1-hydroxyphenanthrene was positively associated with serum E2 levels of females (p-value for trend=0.013). In the adjusted models, no significant association was found between PAHs scores and either T levels of males or E2 levels of females (p-value for trend=0.615, and p-value for trend=0.241, respectively). Conclusions: This study showed urinary 2-hydroxynapthalene and 3-hydroxyfluorene were associated with increased T levels of males, and urinary 1-hydroxyphenanthrene was associated with increased E2 levels of females. The observed association indicated disrupting effects of PAH exposure on reproductive health.